Assessing the efficiency of pacific Asia Islamic stock markets using multifractal detrended fluctuation analysis - Soufiane, Benbachir; Mohamed, Habachi (Edelweiss Applied Science and Technology, 2024)
This paper aims to assess the informational efficiency of six Islamic stock markets in the Asia-Pacific region. To achieve this, the study pursues two specific objectives: first, to capture and quantify the degree of multifractality, and second, to identify the sources of this multifractality within these markets. Utilizing the Multifractal Detrended Fluctuation Analysis (MF-DFA) method, the multifractal behavior of these markets is analyzed. The empirical findings, derived from the application of generalized Hurst exponents, Rényi exponents, and the singularity spectrum, indicate that the six Islamic markets studied display multifractal properties, suggesting a lack of market efficiency. Furthermore, by employing shuffling and phase randomization techniques, it is determined that long-term correlations and heavy-tailed distributions jointly contribute to the observed multifractality. The results of this study have several practical implications for various market stakeholders. Investors should incorporate multifractal analysis into their strategies, focusing on long-term correlations and extreme events to enhance predictive accuracy and risk management. Diversification can help mitigate risk, while remaining vigilant about long-term trends and market patterns. Policymakers should improve market transparency, address inefficiencies, and implement targeted regulations to enhance market stability, such as stress-testing for extreme events and long-term trends. Future research should explore the factors driving multifractality to improve financial models.